1997
DOI: 10.1038/43185
|View full text |Cite
|
Sign up to set email alerts
|

Congenital leptin deficiency is associated with severe early-onset obesity in humans

Abstract: The extreme obesity of the obese (ob/ob) mouse is attributable to mutations in the gene encoding leptin, an adipocyte-specific secreted protein which has profound effects on appetite and energy expenditure. We know of no equivalent evidence regarding leptin's role in the control of fat mass in humans. We have examined two severely obese children who are members of the same highly consanguineous pedigree. Their serum leptin levels were very low despite their markedly elevated fat mass and, in both, a homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
1,491
5
107

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,646 publications
(1,623 citation statements)
references
References 19 publications
20
1,491
5
107
Order By: Relevance
“…We found that leptin levels were undetectable, and that these children were homozygous for a frameshift/premature stop mutation in the leptin gene that prevented all normal leptin production. 29 It is a rare privilege in medical research to identify a new condition that is so obviously amenable to treatment. In these and in seven subsequent children with severe obesity associated with complete leptin deficiency, we have been able (with the support of amgen and subsequently amylin) to administer daily injections with recombinant leptin with remarkably beneficial effects on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…We found that leptin levels were undetectable, and that these children were homozygous for a frameshift/premature stop mutation in the leptin gene that prevented all normal leptin production. 29 It is a rare privilege in medical research to identify a new condition that is so obviously amenable to treatment. In these and in seven subsequent children with severe obesity associated with complete leptin deficiency, we have been able (with the support of amgen and subsequently amylin) to administer daily injections with recombinant leptin with remarkably beneficial effects on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…13 The disabling obesity of leptin deficiency is characterized by the selective deposition of fat and children often develop valgus deformities of the knees by the age of 5-6 y, sleep apnoea and high rates of childhood infection and atopic disease due to abnormalities of T-cell number and function. 14 Hypothalamic hypothyroidism is seen at a young age with a subsequent failure to undergo pubertal development due to hypogonadotropic hypogonadism.…”
Section: Congenital Leptin and Leptin Receptor Deficiencymentioning
confidence: 99%
“…1 Also in humans some cases of extreme obesity are known, which are caused by leptin deficiency, as a result of rare mutations in the leptin gene. 2 Injecting these humans or ob/ob mice with leptin reduces their food intake and brings them back to lower body weight. [3][4][5] Serum leptin concentrations are positively correlated with the amount of fat mass in the body.…”
Section: Introductionmentioning
confidence: 99%